Progestin and adipoQ receptor 7 (PAQR7) mediate the anti-apoptotic effect of P4 on human granulosa cells and its deficiency reduces ovarian function in female mice - Jia Li; Yiting Liu; Jinxia He; Zixuan Wu; Fang Wang; Jian Huang; Liping Zheng; Tao Luo (BMC, 2024)
Abstract Purpose PAQR7 plays a key role in cell apoptosis as a progesterone membrane receptor. The physiological mechanism of PAQR7 in ovarian function and its anti-apoptotic action in mammals remain poorly understood. Methods We first added 0.2 µM aminoglutethimide (AG), an inhibitor of endogenous progesterone (P4) secretion, and transfected siPAQR7 co-incubated with P4 in human KGN cells to identify granulosa cell apoptosis, respectively. Additionally, we used Paqr7 knockout (PAQR7 KO) mice to assess the role of PAQR7 in the ovary. Results The PAQR7 deficiency significantly increased apoptosis of KGN cells, and this significant difference disappeared following P4 supplementation. The Paqr7 −/− female mice showed a prolonged estrous cycle, reduced follicular growth, increased the number of atresia follicles, and decreased the concentrations of E2 and AMH. The litters, litter sizes, and spontaneous ovulation in the Paqr7−/− mice were significantly decreased compared with the Paqr7+/+ mice. In addition, we also found low expression of PAQR7 in GCs from human follicular fluids of patients diagnosed with decreased ovarian reserve (DOR) and ovaries of mice with a DOR-like phenotype, respectively. Conclusions The present study has identified that PAQR7 is involved in mouse ovarian function and fertilization potential. One possible mechanism is mediating the anti-apoptotic effect of P4 on GC apoptosis via the BCL-2/BAX/CASPASE-3 signaling pathway. The mechanism underlying the effect of PAQR7 on ovarian development and aging remains to be identified.